EVI1 carboxy-terminal phosphorylation is ATM-mediated and sustains transcriptional modulation and self-renewal via enhanced CtBP1 association - Paredes, Roberto; Löffler, Harald (Nucleic acids research, 2018)
Abstract. The transcriptional regulator EVI1 has an essential role in early hematopoiesis and development. However, aberrantly high expression of EVI1 has pote
Gesehen am 21.02.2020